TEACHING ALLO-REPETITION STRATEGY TO IMPROVE STUDENTS’ PARTICIPATION IN CONVERSATION CLASS - Enggrasedes, Enggrasedes (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2009)
This paper describes how allo-repetition strategy improves students’ participation in conversation class. Students’ low participation in conversation class is presumably caused by their having no strategy in speaking. This research is aimed at examining whether allo-repetition strategy can better improve students’ participation in English conversation. The kind of research is a Classroom Action Research conducted in two cycles at grade X2 which consisted of 31 students. The data were collected by using observation sheets, field notes, and tape recordings. The qualitative data were analyzed by using the technique suggested by Hopkins (1993: 159-162), and the quantitative data were analyzed by using percentage. The result of data analysis from observation sheets and field-notes show the improvement of students’ involvement in learning process. The data from students’ recorded conversation show the improvements in terms of numbers of exchanges the students could produce in a conversation, students’ turn-taking, and students’ back-channeling. The result of this research indicates that allo-repetition strategy better improves students’ participation in conversation class. Key words/ phrases: allo-repetition, conversation class, speaking, turn- taking, back-channel